The new realities : in government and politics, in economics and business, in society and world view - Drucker, Peter F. (Peter Ferdinand), 1909-2005. (Oxford : Butterworth-Heinemann Ltd., 1989)
Analyzes the new limits and functions of government, the changing demands on political leadership, and the transnational economy and ecology.
pt. 1. The political realities. The divide -- No more salvation by society -- The end of FDR's America -- When the Russian empire is gone -- Now that arms are counterproductive -- pt. 2. Government and political process. The limits of government -- The new pluralisms -- Beware charisma: the changed demands on political leadership.
Includes index.
Keywords: World politics -- 1985-1995.; Economic history -- 1971-1990.; Information society